Efficiency-Based Training Budgeting Strategy (Case Study at Patut Patuh Patju Hospital, West Lombok Regency) - Maria, Evi; Purwadhi, Purwadhi; Mulyani, Kahar (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the budgeting strategy of efficiency-based training at Patut Patuh Patju Hospital, West Lombok Regency. The approach used is qualitative descriptive through interviews, observations, and documentation of parties involved in planning, managing, and evaluating training budgets. Data analysis was carried out interactively using the Miles and Huberman model which included data reduction, data presentation, and conclusion drawn. The main focus of this research is to understand how the process of planning and preparing training budgets is carried out, the obstacles faced, the efforts taken to overcome them, and the hospital development strategy based on the current financial conditions. The results of the study show that the process of planning and preparing training budgets at Patut Patuh Patju Hospital is carried out systematically through the annual Training Need Assessment (TNA) mechanism, although it is not completely based on the evaluation of training results. The main obstacle faced is budget limitations due to financial rationalization and suboptimal coordination between departments. Efforts to overcome obstacles are carried out through budget efficiency, postponement of non-priority training, utilization of internal resources, and collaboration with external institutions through webinar-based online training. The hospital development strategy is directed at optimizing human resources and strengthening the training system based on actual needs, accompanied by continuous performance evaluation and the use of technology to support the effectiveness of training.